2012
DOI: 10.1128/aem.01287-12
|View full text |Cite
|
Sign up to set email alerts
|

Host Preferences of Arbuscular Mycorrhizal Fungi Colonizing Annual Herbaceous Plant Species in Semiarid Mediterranean Prairies

Abstract: In this study, we have analyzed and compared the diversities of the arbuscular mycorrhizal fungi (AMF) colonizing the roots of five annual herbaceous species (Hieracium vulgare, Stipa capensis, Anagallis arvensis, Carduus tenuiflorus, and Avena barbata) and a perennial herbaceous species (Brachypodium retusum). Our goal was to determine the differences in the communities of the AMF among these six plant species belonging to different families, using B. retusum as a reference. The AMF small-subunit rRNA genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
83
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 52 publications
11
83
1
2
Order By: Relevance
“…A higher species richness than in our study was detected in Mediterranean semi-arid environments (Torrecillas et al 2012). Using a morphological approach, a previous study on the occurrence of AMF spores in an organic field located in the same area detected a very high number of AMF species (58), never reported from a single site (Njeru et al 2015).…”
Section: Identification Of Root Colonizing Amfmentioning
confidence: 52%
“…A higher species richness than in our study was detected in Mediterranean semi-arid environments (Torrecillas et al 2012). Using a morphological approach, a previous study on the occurrence of AMF spores in an organic field located in the same area detected a very high number of AMF species (58), never reported from a single site (Njeru et al 2015).…”
Section: Identification Of Root Colonizing Amfmentioning
confidence: 52%
“…This is a high level of AMF community richness considering that only a single plant species was studied. In previous studies focusing on much more diverse plant communities in semiarid Mediterranean ecosystems (17)(18)(19), we have found values for AMF community richness in individual plant species ranging between 8 and 20. All samples from epiphytic plants showed AMF sequences, thus confirming that S. tenerrimus epiphytic plants establish a symbiotic relationship with AMF.…”
Section: Discussionmentioning
confidence: 99%
“…Zangaro et al (2008Zangaro et al ( , 2013 showed that root colonization and spore density decreased among successional stages from grasslands to mature forests and different stages in plant age and succession also influence the AMF communities (Husband et al 2002;Aldrich-Wolfe 2007). Other studies indicate host preferences (Scheublin et al 2004;Sýkorová et al 2007;Torrecillas et al 2012;Yang et al 2012). In general, standardized analyses, possibly based on the methods presented here, may allow a more robust interpretation and comparison of such data in the future.…”
Section: Influence Of Plant Stage and Altitude On Amf Species Communimentioning
confidence: 99%